Progesterone Regulates Secretin Expression in Mouse Uterus During Early Pregnancy. (June 2014) - Huang, Zhu; Wang, Tong-Song; Qi, Qian-Rong; Zuo, Ru-Juan; Liang, Xiao-Huan; Zhao, Xu-Yu; Yang, Zeng-Ming
Secretin, a classical gastrointestinal and neuroendocrine peptide, plays an important role in maintaining the body fluid balance. However, the expression and regulation of secretin in the reproductive system are still unknown. In our study, secretin is specifically expressed in the decidua on days 5 to 8 of pregnancy. Secretin expression is not detected under delayed implantation but is stimulated after estrogen activation and under artificial decidualization. Progesterone induces secretin expression in ovariectomized mice and cultured stromal cells, which is abrogated by specific LY294002. Because secretin is mainly localized in the decidua and also strongly expressed during in vitro decidualization, secretin may play a role during mouse decidualization through regulating cyclic adenosine monophosphate level.